Baran-Szołtys, M., Glosowitz, M. and Konarzewska, A. (eds.): Imagined Geographies: Central European Spatial Narratives between 1984 and 2014 - Kronstein, Bálint (Hungarian Geographical Bulletin, 2020)
-